Comparison of home made and commercial rapid urease tests for detection of helicobacter pylori in patients with gastroduodenitis and peptic ulcer - Sharma, Yuba Raj; Wagley, Amrita; Singh, Sunil (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Helicobacter pylori is one of the common and medically prominent infections worldwide and an established etiological factor for peptic ulcer disease. This study was conducted to compare the results of two types of Rapid Urease Tests (RUT) for H. pylori infection. Methods: This study was conducted in patients with gastro duodenal diseases visiting Kantipur Hospital from June to August 2010. Antral biopsies were collected from sixty patients visiting endoscopy unit. The diagnosis was of H. pylori infection carried out using two types of rapid urease tests (commercial and homemade) as well as Histopathology. Results: H. pylori infection was detected in 34 (56.67%) of 60 by histological test, 24 (40%) by homemade kit method and 28 (46.67%) by commercial RUT method. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for RUT (commercial kit) considering histology as gold standard were 76.74%, 92.31%, 92.85% and 75% respectively. The sensitivity, specificity, PPV and NPV for RUT (homemade kit) were 58.82%, 84.62%, 83.3% and 61.11% respectively. Conclusions: Homemade rapid urease test was sensitive and specific for detection of H. pylori infection than commercial test.